2021
DOI: 10.1001/jamanetworkopen.2021.14494
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Randomized Clinical Trials in Surgery From 2008 to 2020

Abstract: IMPORTANCE Randomized clinical trials (RCTs) provide the highest level of evidence to evaluate 2 or more surgical interventions. Surgical RCTs, however, face unique challenges in design and implementation. OBJECTIVE To evaluate the design, conduct, and reporting of contemporary surgical RCTs. EVIDENCE REVIEW A literature search performed in the 2 journals with the highest impact factor in general medicine as well as 6 key surgical specialties was conducted to identify RCTs published between 2008 and 2020. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 28 publications
1
45
0
Order By: Relevance
“…This setting likely explains many of the encountered challenges regarding low-quality—often non-RCT evidence—and the need for indirect comparison across treatments. A recent review of RCTs in surgery by Robinson et al [ 33 ] concludes that more than half of the reviewed RCTs had some concern with bias and about 20% had high risk of bias—a finding we may confirm. Also, Robinson et al report that about 80% of RCTs did not control for surgeon experience.…”
Section: Discussionmentioning
confidence: 66%
“…This setting likely explains many of the encountered challenges regarding low-quality—often non-RCT evidence—and the need for indirect comparison across treatments. A recent review of RCTs in surgery by Robinson et al [ 33 ] concludes that more than half of the reviewed RCTs had some concern with bias and about 20% had high risk of bias—a finding we may confirm. Also, Robinson et al report that about 80% of RCTs did not control for surgeon experience.…”
Section: Discussionmentioning
confidence: 66%
“…Two previous studies reported the risk of bias and reporting quality of included trials with the results of PRECIS-2 assessments. 18 19 However, since this study will evaluate the methodological features of trials in terms of pragmatism rather than reporting the clinical effect of interventions or quality of trials, assessing the risk of bias and reporting quality would be non-essential. (2) Search terms that could mean pragmatic intention are not included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of this study are as follows: (1) This study will not assess the risk of bias and reporting quality. Two previous studies reported the risk of bias and reporting quality of included trials with the results of PRECIS-2 assessments 18 19. However, since this study will evaluate the methodological features of trials in terms of pragmatism rather than reporting the clinical effect of interventions or quality of trials, assessing the risk of bias and reporting quality would be non-essential.…”
Section: Discussionmentioning
confidence: 99%
“…While other trials 54.6% reported a neutral result; reporting bias was identified in 51.7%. Multiplicity was detected in 45.1%, and only 20.0% adjusted for multiple comparisons ( 76 ). In another trial, 117 individuals were randomized between control (surgery alone), intra-arterial chemotherapy and systemic chemotherapy.…”
Section: Summary Of Trials and Its Major Changesmentioning
confidence: 99%